Inter-Limb Muscle Synergies and Kinematic Analysis of Hands-and-Knees Crawling in Typically Developing Infants and Infants With Developmental Delay - Xiong, Qi L.; Wu, Xiao Y.; Yao, Jun; Sukal-Moulton, Theresa; Xiao, Nong; Chen, Lin; Zheng, Xiao L.; Liu, Yuan; Hou, Wen S. (Frontiers in Neurology, 2018)
Hands-and-knees-crawling is an important motor developmental milestone and a unique window into the development of central nervous system (CNS). Mobility during crawling is regularly used in clinical assessments to identify delays in motor development. However, possible contribution from CNS impairments to motor development delay is still unknown. The aim of this study was to quantify and compare inter-limb muscle synergy and kinematics during crawling among infants at a similar developmental age, however, clinically determined to be typically developing (TD, N = 20) infants, infants at risk of developmental delay (ARDD, N = 33), or infants with confirmed developmental delay (CDD, N = 13). We hypothesized that even though all of the groups are at a similar developmental age, there would be differences in kinematic measures during crawling, and such differences would be associated with CNS impairment as measured by electromyography (EMG) features. Surface EMG of eight arm and leg muscles and the corresponding joint kinematic data were collected while participants crawled on hands and knees at their self-selected velocity. Temporal-spatial parameters and normalized Jerk-Cost (JC) function (i.e., smoothness of movement) were computed from the measured kinematics. The inter-limb muscle synergy and the number of co-activating muscles per synergy were measured using EMGs. We found that the infants with CDD demonstrated higher normalized JC values (less movement smoothness), fewer muscle synergies, and more co-activating muscles per synergy, compared to infants with TD (p < 0.05) and ARDD (p < 0.05). Furthermore, the normalized JC values were correlated (p < 0.05) with the number of co-activation muscles per synergy. Our results suggest a constrained neuromuscular control strategy due to neurological injury in infants with CDD, and such constrain may contribute to the reduced movement smoothness in infant crawling.